Application of Geographic Information System in Identification of ’Fire-Prone’ Areas - a Feasibility Study in Parts of Junagadh (Gujarat) - Kandya, A. K.; Kimothi, M. M.; Jadhav, R. N.; Agarwal, J. P. (Indian Forester, 1998)
Occurrcnce of frequent fire is one of the reasons for degradation of forests in the country/ elsewhere in the world. The forest fires affect (a) standing vegetation, (b) soil, (c) productive capacity of the forest, (d) productive value of the forest, (e) wildlife and (f) recreational. Or scenic values. An attempt has been made to map the fire-prone areas of a part of Junagadh District of Gujarat. IRSIB, LISS-II data were visually classified to ascertain the vegetation status of the study area. The roadnetwork and the huts/settlements were mapped through the Survey ofIndia (SoI) topographical map. Finally, to begin with, these three parameters out of many, which may have direct/indirect influence over the occurrence of fire, were integrated using Geographic Information System (GIS) approach resulting in a ’fire-prone’ map of the area.